2022
DOI: 10.1083/jcb.202109144
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial contribution to anti-inflammatory shear stress signaling in vascular endothelial cells

Abstract: Atherosclerosis, the major cause of myocardial infarction and stroke, results from converging inflammatory, metabolic, and biomechanical factors. Arterial lesions form at sites of low and disturbed blood flow but are suppressed by high laminar shear stress (LSS) mainly via transcriptional induction of the anti-inflammatory transcription factor, Kruppel-like factor 2 (Klf2). We therefore performed a whole genome CRISPR-Cas9 screen to identify genes required for LSS induction of Klf2. Subsequent mechanistic inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 67 publications
3
39
0
Order By: Relevance
“…Much has been done to understand transcriptional responses to flow most of these have been focused on early responses in the absence of in vivo genetically-matched counterparts (42)(43)(44)(45)(46)(47). Our data found agreement with previous findings of short time exposure to shear stress, in particular, we noted an impressive induction of KLF2 and KLF4 (48). However, longer exposure to laminar flow (8, 24, 48hrs) progressively increased the resemblance to the ex vivo transcriptome, as noted by correlation coefficients.…”
Section: Discussionsupporting
confidence: 93%
“…Much has been done to understand transcriptional responses to flow most of these have been focused on early responses in the absence of in vivo genetically-matched counterparts (42)(43)(44)(45)(46)(47). Our data found agreement with previous findings of short time exposure to shear stress, in particular, we noted an impressive induction of KLF2 and KLF4 (48). However, longer exposure to laminar flow (8, 24, 48hrs) progressively increased the resemblance to the ex vivo transcriptome, as noted by correlation coefficients.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, regulation of MCU channel activity by the local hemodynamics was recently shown to play a critical role in EC mitophagy and inflammation (Coon et al, 2022 ): SS applied on cultured mouse aortic ECs was shown to activate Erk5, cause a transient increase followed by a sustained decrease in mitochondrial fragment counts (due to activation of mitophagy), upregulate Klf2 and suppress NF‐κB transcriptional activity and inflammatory signaling. Deletion of the essential MCU complex gene Emre blocked the SS effects on EC signaling suggesting that the SS‐induced MCU‐mediated m Ca 2+ influx, via activation of Erk5 kinase, mitophagy, and Klf2 ‐mediated gene expression ( eNOS is a downstream transcriptional target of Klf2 ), regulates mitochondrial homeostasis and establishes the atheroprotective EC phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The atheroprotective effect of s‐flow is majorly due to upregulation of the transcription factor Krüppel‐like factor 2 ( Klf2 ) and its downstream target endothelial nitric oxide (NO) synthase ( eNOS ) that produces the vasodilator NO (Wang et al, 2006 , 2010 ). It was recently shown in vivo (and in vitro) that the MCU‐mediated m Ca 2+ influx is necessary for s‐flow (SS)‐induced EC mitophagy, which contributes to Klf2 expression and the resultant suppression of inflammation (Coon et al, 2022 ). In contrast, ECs exposed to d‐flow (OS), due to their defective mitophagy, did not upregulate Klf2 and instead expressed inflammatory markers (Coon et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To systematically unravel the molecular pathways affecting Klf2 expression under flow, Coon and colleagues ( 3 ) employed a high throughput CRISPR knockout (KO) approach in conjunction with in vitro perfusion endothelial cell culture and an ingenious synthetic Klf2 reporter. Expressed under the control of the Klf2 promoter, a modified GFP with a half-life similar to that of Klf2 protein allowed accurate quantification of Klf2 expression in live experiments while knocking out single genes.…”
mentioning
confidence: 99%